The type specimens of Anthomyiidae, Muscidae and Sarcophagidae (Diptera: Calyptratae) housed at the Instituto – Fundación Miguel Lillo, Tucumán, Argentina - Patitucci, Luciano D. (2011)
Fil: Patitucci, Luciano D. Consejo Nacional de Investigaciones Científicas y Técnicas, Buenos Aires; Argentina